PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Maria Viola Syaloomita (2023)
This research uses quantitative research where it aims to see if there are any effects of corporate social responsibility and profitability on firm value. The population used in this study are mining companies that are listed on Indonesia Stock Exchange from 2017 to 2021, and the amount of samples obtained are 60 samples by using the purposive sampling method to decide the sample. The analysis method in this study is multiple linear regression analysis ran by STATA version 14, where the results of tested hypotheses are stated that return on asset has a significant and positive effect on firm value, while corporate social responsibility and net profit margin do not have any significant effect on firm value.